2014
DOI: 10.1155/2014/631380
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Obstructive Sleep Apnea Syndrome and Cardiac Disease Severity

Abstract: Background. Obstructive sleep apnea (OSA) syndrome is one of the most common respiratory disorders in humans. There is emerging evidence linking OSA to vascular disease, particularly hypertension. The underlying pathophysiological mechanisms that link OSA to cardiovascular diseases such as hypertension, congestive heart failure, and atrial fibrillation are not entirely understood. The aim of this study was to investigate the association of obstructive sleep apnea hypopnea syndrome (OSAHS) with coronary atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Probably the difference between the findings can be due to the kind of study, the age of the subjects, selecting only males, and suffering from a systolic kind of heart failure in the current study and the difference in OSA evaluation method. Change and increase in the probability of OSA was observed in older patients more than in the younger ones (35). Probably poor function of muscles of holding the airway open has a role in increasing apnea in the aged people.…”
Section: Discussionmentioning
confidence: 87%
“…Probably the difference between the findings can be due to the kind of study, the age of the subjects, selecting only males, and suffering from a systolic kind of heart failure in the current study and the difference in OSA evaluation method. Change and increase in the probability of OSA was observed in older patients more than in the younger ones (35). Probably poor function of muscles of holding the airway open has a role in increasing apnea in the aged people.…”
Section: Discussionmentioning
confidence: 87%
“…The literature on sleep and HIV and neurocognition had focused on the CNS effects of efavirenz but this effect on sleep and neurocognition can be variable in duration [ 147 ]. Sleep disorders are also associated with other medical conditions including metabolic syndrome and cardiovascular disease [ 148 152 ]. The synergistic effect of sleep disorders and cardiovascular and metabolic complications on neurocognition in HIV patients has not been reported extensively.…”
Section: Physical Comorbidities Effecting Cognitionmentioning
confidence: 99%
“…In an another study conducted on patients with acute coronary syndrome, more chronic total occlusion lesions were detected in OSAS patients compared to patients without OSAS [19]. It has been reported that multivessel disease and coronary artery calcification are more common in OSAS patients [20][21][22]. In our study we investigated whether there is a specific relationship between SX score and OSAS patients and coronary segments.…”
Section: Discussionmentioning
confidence: 83%